(untitled) (Journal of Current and Advance Medical Research, 2021)
Background: Different pathology of breast is found among the women. Objective: The purpose of the present study was to see the profiles of breast disease among women seeking for treatment during Covid-19 pandemic at the OPD of medical university of Bangladesh. Methodology: This descriptive cross-sectional study was conducted in the Department of Surgery at Bangabandhu Shiekh Mujib Medical University, Dhaka, Bangladesh from 1 April to 31 October 2020 for a period of six months. All the women who were attended at the OPD of the Department of Surgery with the different complaints of breast at any age were selected as study population. The different disease profiles were recorded in the data sheet. Result: A total number of 1625 women were recruited for this study. The mean age with standard deviation of the study population was 36.4±12.54 years. Among 1492 women the most common breast complaints was mastalgia which was 492(29.9%) cases followed by fibrocystic disease, breast lump, fibroadenoma and carcinoma breast which was 296(18.0%) cases, 202(12.3%) cases, 141(8.6%) cases and 84(5.1%) cases respectively. Similarly duct ectasia, fibroadenoma, fibrocystic disease and lipoma were also most common among the less than or equal to 45 years age group of women which were 47(94.0%) cases, 137(97.2%) cases, 269(90.9%) cases and 75(51.4%) cases respectively. Conclusion: In conclusion breast lump and fibrocystic disease are the most common diseases among the women attending during covid19 era. Journal of Current and Advance Medical Research, January 2021;8(1):3-6